C. R. Rao's century. Issue 4 (29th July 2020) - Efron, Bradley; Amari, Shun‐ichi; Rubin, Donald B.; Rao, Arni S. R. Srinivasa; Cox, David R.
Abstract : On 10 September 2020, C. R. Rao turns 100. Bradley Efron, Shun‐ichi Amari, Donald B. Rubin, Arni S. R. Srinivasa Rao and David R. Cox reflect on his contributions to statistics Abstract : On 10 September 2020, C. R. Rao turns 100. Bradley Efron, Shun‐ichi Amari, Donald B. Rubin, Arni S. R. Srinivasa Rao and David R. Cox reflect on his contributions to statistics.